The Influence of Leadership, Work Discipline, and Work Motivation on Employee Performance (Study at Tegowanu District Office) - Hertiana, Maghfiroh; Miftanudin, Arif; Agustin, Indah Ratna; Souisa, Johanis (PT FORMOSA CENDEKIA GLOBAL, 2025)
Performance denotes the outcomes produced by employees, encompassing both quality and quantity, in executing activities aligned with their assigned responsibilities. Organizations must implement numerous measures to enhance employee performance in order to attain these aims. Research subject of the Tegowanu District Office, Grobogan, Central Java. The data indicates that multiple employees arrive late to work without justification, suggesting suboptimal employee performance. Numerous factors can influence employee performance, including leadership, work discipline, and motivation. This study aims to examine the impact of leadership, work discipline, and work motivation on employee performance. The study's demographic and sample comprised all 34 workers of the Tegowanu District Office. The chosen sampling approach was a saturated sample. The data utilized was primary. The data collection approach employed a questionnaire. This research employs several linear regression analysis approaches. The analysis indicates that leadership exerts a favorable and significant influence on employee performance (sig. 0.015 < 0.05). Work discipline exerts a positive and significant influence on employee performance (sig. 0.014 < 0.05). Work motivation exerts a positive and significant influence on employee performance (sig. 0.025 < 0.05).